Ca and Ce Effect on the Corrosion Resistance of Hot-Rolled AZ31 Mg Alloys - Kara, I. H.; Yousef, T. A. I.; Ahlatci, H.; Turen, Y. (Engineering, Technology & Applied Science Research, 2020)
In this study, AZ31 Mg alloys with added Ca and Ce were produced by low pressure die casting and were rolled at 400°C. The corrosion properties of the materials were determined by immersion test for 72 hours at a 3.5% NaCl solution. The microstructure of the samples was investigated by light optical microscopy (LOM) and scanning electron microscopy (SEM) before the corrosion test. Twins, dynamic recrystallization (DRX), and the alloying elements have an important role in imparting the final corrosion resistance of the investigated materials.